Strategi Pengembangan Pendidikan Karakter di MTs Mashlahatul Hidayah - Rugaya Meis Andhiarini; Amrozi Amrozi; Supeno Supeno (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2020)
The purpose of this study is to know the strategy of implementing character education to students and support factors and inhibitors in MTS Mashlahatul Hidayah, in the hope of providing new innovations in the world of education how character education strategies.This research is a qualitative research by expressing field findings by thrilling thoroughly about data obtained in field, method of data collection in this study using interview techniques, observation and documentation, in this case the researcher analyzed data through. 1) data collection, 2) data reduction, 3) data presentation, 4) withdrawal conclusions.The results showed the values of priority character education were 1) Religious characters, with the form of a) Salat Zuhur congied, b) Ngaji Yasin before KBM. 2) Character of the man with a form of activity A) Salim, b) pending, c) down from the motor. 3) discipline characters. 4) character of environmental love.